1976
DOI: 10.2466/pms.1976.43.2.663
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Item Arrangement on Perceived Numerosity: Randomness vs Regularity

Abstract: Subjects were shown pairs of dot patterns, a regular one and a randomly arranged set, and were asked to say which appeared more numerous. In three experiments using 53 college students regular patterns appeared significantly more numerous than random arrays, with an average illusion of 5.5%. The results were discussed in relation to the breakdown of conservation of number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
81
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 6 publications
9
81
0
Order By: Relevance
“…An example of the effect of spatial distribution on these judgments is the "regular-random illusion" reported by Ginsburg (1976). He found that human observers estimated a display of evenly spreadout dots to be more numerous than a random distribution of the same number of dots.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of the effect of spatial distribution on these judgments is the "regular-random illusion" reported by Ginsburg (1976). He found that human observers estimated a display of evenly spreadout dots to be more numerous than a random distribution of the same number of dots.…”
Section: Methodsmentioning
confidence: 99%
“…In the third type of array, the items were more spread out. Their spacing was irregular, so that although the experimenters chose the item locations, the arrays resembled the "random" arrays that Ginsburg (1976) used, rather than his "regular" arrays. Since the parameters of the stimulus arrays were all specified in coding files, van Oeffelen and Vos's (1983) CODE algorithm could subsequently be applied to the stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…The ANS can process numerosities presented or produced both serially and simultaneously (Cordes, Gelman, Gallistel, & Whalen, 2001;Meck & Church, 1983;Revkin et al, 2008;Taves, 1941). ANS estimations can be influenced by perceptual factors, such as regularity of spacing (Ginsburg, 1976(Ginsburg, , 1978Taves, 1941), perceived area (van Oeffelen & Vos, 1982Vos, van Oeffelen, Tibosch, & Allik, 1988), and item segmentation (Franconeri et al, 2009). While some claim that ANS estimations are based solely on continuous extent features, such as area and density (Mix, Huttenlocher, & Levine, 2002), other research indicates that the ANS can assess numerosity even when continuous extent is controlled (Cordes & Brannon, 2008;Hurewitz, Gelman, & Schnitzer, 2006).…”
Section: Visual Nesting Impacts Approximate Number System Estimationmentioning
confidence: 99%
“…For example, objects occupying a more extended area on the display usually appear to contain more numerous elements (Bevan, Maier, & Helson, 1963;Binet, 1890;Ponzo, 1928). Many other configurations of dots have been found to increase or decrease in their apparent visual number, relative to the same number of randomly distributed dots (Frith & Frith, 1972;Ginsburg, 1976;Ginsburg & Goldstein, 1987; The authors thank Norman Ginsburg, Tarow Indow, and an anonymous reviewer for helpful comments on an earlier version of this article. The discussion of this research topic with Piet Vos has been very stimulating for many years.…”
mentioning
confidence: 99%